Undesirable risks of ozone-resistant bacteria (ORB): biofilm formation potentials and control strategy - Hao-Bin Wang; Yin-Hu Wu; Yuan Bai; Zhuo Chen; Rui-Ning Wang; Han Liu; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2026)

Multi-task molecular representation learning based on soft prompting of the important subgraph - Yupeng Liu; Han Zhang; Rui Hu; Hui Zhang; Xiaochen Zhang (Molecular Genetics and Genomics, 2026)

Microwave coupled ultrasound pretreatment for enhancing acid leaching of ilmenite and its mechanism - Rui Liu; Long Xiang; Tao Long; Wenrong Xiang; Jiahao Hu; Li Li; Chunhui Han; Xingran Zhang (Minerals Engineering, 2026)

Stage-resolved zinc isotope dynamics in firefighters’ hair after firefighting - Ziyang Ding; Guilin Han; Qian Zhang; Rui Qu; Jian Hu; Di Wang; Wenqian Sun; Ye Zhao (Journal of Hazardous Materials, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

A voyage-level threshold analysis of planned turnaround vulnerability in cruise ports from an AIS big data perspective - Shengjun Gan; Shikai Hu; Han Zhang; Kai Luo; Rui Yang; Salvatore Antonio Biancardo (Frontiers in Marine Science, 2026)
Introduction Cruise port operations are facing increasingly significant challenges in departure reliability amid frequent climate variability, port congestion, supply chain disruptions, and geopolitical risks. Unlike existing studies that mainly explain cruise delays from the perspectives of weather conditions, external shocks, or supply chain risks, this paper focuses on whether port turnaround planning itself may constitute an endogenous source of vulnerability. Methods To identify this issue, this study uses the daily AIS data for the United States released by Marine Cadastre. These data are combined with planned berthing information, weather data, and vessel characteristics to construct a sample of 3,238 cruise ship–port–day observations. The study defines planned turnaround time as a time-based buffer resource in voyage-level operations. It then applies a fixed effects model, a threshold regression model, a half-hour interval model, mechanism tests, heterogeneity analysis, and moderation analysis to systematically examine the impact of planned turnaround time on departure reliability and its operational boundaries. Results The results show a significant threshold-type nonlinear relationship between planned turnaround time and departure delay. An 8.5-hour threshold is identified as the main data-driven cutoff, while a meaningful buffering effect is mainly observed within 8 hours. The interval of 8.0–8.5 hours is better viewed as a transition range where marginal benefits begin to decline. Mechanism tests indicate that actual berthing service time is the most stable primary transmission channel of planned turnaround vulnerability, while port queuing pressure and berth occupancy pressure further modify the marginal effect of planned turnaround time. Discussion This study moves the analysis of cruise departure delays from explanations based on exogenous shocks to the identification of endogenous vulnerability. By revealing that planned turnaround time itself can become a source of risk under specific threshold conditions, these findings complement existing resilience literature that has primarily focused on external drivers. It provides new micro-level evidence for understanding the resilience of cruise port operations, optimizing schedule planning, and improving port coordination efficiency.

Baseline and fractionation of rare earth elements in hair of urban residents in Nanning, South China - Hongcheng Mei; Ziyang Ding; Guilin Han; Rui Qu; Xiaoyu Hu; Di Wang; Zhaowei Jie; Wenqian Sun; Jun Zhu (Environmental Geochemistry and Health, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

BTEXS metabolites and lung dysfunction in petrochemical workers: Dose-response relationships and the mediation of oxidative stress - Dongsheng Wang; Rui Ma; Minghui Xiao; Zhaorui Zhang; Han Yang; Yanrong Lv; Shaorui Yu; Xiumei Xing; Shanfeng Dang; Qifei Deng; Xiaoyu Mao; Qiansheng Hu; et al. (Atmospheric Pollution Research, 2026)

Ablation of FBXO38 triggers lysosome-dependent STING degradation to drive chemotherapy resistance in cervical cancer - Xihua Shen; Qi Liu; Yan Li; Xiaoping Ma; Cengceng Lu; Rongyan Ma; Rui Han; Zhiyi Lin; Hu Han (Apoptosis, 2026)

Realization of elastic Weyl semimetal phases with skyrmion spin textures - Yuang Pan; Liang Si; Miao Yang; Ning Han; Li Zhang; Qiaolu Chen; Rui Zhao; Fujia Chen; Yudong Ren; Wenhao Li; Yuze Hu; Mingyu Tong; et al. (Science Bulletin, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

SEAF-Net: A Sustainable and Lightweight Attention-Enhanced Detection Network for Underwater Fish Species Recognition - Yu-Shan Han; Sheng-Lun Zhao; Chu Chen; Kangning Cui; Pingfan Hu; Rui-Feng Wang (Journal of Marine Science and Engineering, 2026)
This study presents SEAF-Net, a lightweight and efficient detection network designed for low-contrast and highly dynamic underwater environments. Built upon YOLOv11n, SEAF-Net introduces three complementary structural enhancements: (1) Omni-Dimensional Dynamic Convolution (ODConv) to improve adaptive modeling of multi-scale and directional texture variations; (2) SimA-SPPF, which embeds the SimAM attention mechanism into the SPPF module to enable neuron-level saliency reweighting and effective suppression of complex background interference; and (3) GhostC3k2 to reduce redundant computation while preserving sufficient representational capacity. Evaluated on a standardized 13-class underwater fish dataset under a unified training and evaluation protocol, SEAF-Net achieves 6.1 GFLOPs, 92.683% Precision, 88.459% Recall, 93.333% mAP50, 73.445% mAP, and a 90.522% F1-score. Compared with the YOLOv11n baseline, SEAF-Net improves F1-score and Recall by 0.510% and 0.575%, respectively, while reducing computational cost by approximately 6%, demonstrating a favorable accuracy–efficiency trade-off under lightweight constraints. Ablation results further confirm that SimA-SPPF plays a dominant role in background suppression, ODConv consistently enhances deformation and directional texture modeling, and GhostC3k2 effectively controls computational overhead without degrading detection accuracy. To assess deployment feasibility, additional test set evaluations were conducted under deployment-oriented conditions using resource-limited hardware, yielding an F1-score of 88.54%. This result confirms that the proposed model maintains stable detection performance and robustness beyond training and validation stages. Overall, SEAF-Net provides an effective balance of accuracy, efficiency, and robustness, offering practical support for low-carbon, scalable, and sustainable intelligent aquaculture monitoring and underwater ecological assessment in real-world environments.

Noise Characteristics and Shallow Subsurface Structure Detection in Coastal Zones: A Case Study from Dong’ao Island, Zhuhai - Siqing Liu; Sixu Han; Yongzhi Liang; Shuji Yang; Yi Chai; Tongying Hu; Ruifeng Wu; Yu Li; Qingxian Zhao; Zengjia Li; Wei Zhang; Xianqing Wang; et al. (Journal of Marine Science and Engineering, 2026)
Shallow subsurface structure detection in coastal zones serves as a critical foundation for resource development and engineering construction. However, conventional geophysical methods exhibit significant limitations in land–sea transition zones, where pronounced “boundary effects” create substantial “exploration gaps” due to difficulties in merging terrestrial and marine datasets. To achieve truly seamless subsurface imaging across the coastal boundary, this study develops and implements an integrated cross-boundary survey approach utilizing nodal seismometers and seismic ambient noise. At Dong’ao Island, Zhuhai, we deployed a comprehensive seismic profile spanning hillside, sandbeach, and seafloor environments to evaluate the method’s applicability in complex coastal settings systematically. Results demonstrate substantially stronger ambient noise energy in submarine environments compared to terrestrial settings. All stations recorded abundant and stable high-frequency (>1 Hz) noise signals, which are adequate for shallow subsurface imaging. Rayleigh wave dispersion curves extracted via the advanced Frequency-Bessel transform method enabled inversion of a continuous 2D shear-wave velocity profile along the survey line. Bedrock interface depths determined using the Horizontal-to-Vertical Spectral Ratio (HVSR) method showed remarkable consistency with the bedrock morphology revealed by the shear-wave velocity structure, validating the reliability of our approach in coastal environments. This research successfully demonstrates the feasibility of seismic ambient noise imaging as a bridging technique for land–sea exploration, providing an efficient, environmentally friendly, and continuous technical solution to overcome coastal zone exploration challenges.

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

A Hybrid CUBE-IForest Approach for Outlier Detection in Multibeam Bathymetry - Rui Han; Yukai Hong; Xibin Han; Yi Zhang; Shunming Hu; Yuan Huan; Xiaodong Cui; Xiaohu Li (Journal of Marine Science and Engineering, 2026)
With the rapid development and widespread application of multibeam echo-sounding systems, large-scale and high-resolution seafloor topography can be efficiently acquired, enabling precise mapping of seabed terrain. However, due to complex oceanographic conditions, instrumental noise, and acoustic interferences, the acquired multibeam data often contain outliers that deviate from the true seafloor surface. These outliers can distort the representation of seafloor topography, adversely affecting subsequent geological analysis and engineering applications. To address this issue, a hybrid outlier detection method combining CUBE filtering with the Isolation Forest (IForest) algorithm, termed CUBE-IForest, is proposed. The method first employs CUBE filtering to remove gross outliers based on local uncertainty estimation, followed by the application of IForest to identify subtle anomalies in the refined data, achieving hierarchical detection of outliers. Experimental results based on in situ multibeam bathymetric data from the northeastern Pacific demonstrate that compared with traditional filtering methods the CUBE-IForest approach significantly improves detection accuracy and reduces both false positive and false negative rates by approximately 30%, confirming its efficiency and reliability in seafloor mapping and analysis.

A unified hybrid deterministic-stochastic inversion methodology - Chao Zhuang; Long Yan; Huiyang Qiu; Rui Hu; Jiangbo Han; Huan Song; Zhifang Zhou; Jinguo Wang; Walter A. Illman (Journal of Hydrology, 2026)